Incidence of New-Onset and Worsening Heart Failure Before and After the COVID-19 Epidemic Lockdown in Denmark: A Nationwide Cohort Study. (June 2020) - Andersson, Charlotte; Gerds, Thomas; Fosbøl, Emil; Phelps, Matthew; Andersen, Julie; Lamberts, Morten; Holt, Anders; Butt, Jawad H.; Madelaire, Christian; Gislason, Gunnar; Torp-Pedersen, Christian; Køber, Lars; et al.
Abstract : Background: The Danish government ordered a public lockdown on March 12, 2020, because of the coronavirus disease 2019 (COVID-19) pandemic. We investigated the immediate consequences of such a lockdown for patients with heart failure (HF). Methods: Using the Danish nationwide administrative databases, we investigated the incidence of new-onset HF and hospitalizations for worsening HF before and after the lockdown (January 1 to March 11 versus March 12 to March 31) in 2020 versus 2019. We also investigated the mortality for all patients with HF and in COVID-19–infected patients with HF. Results: Rates of new-onset HF between January 1 and March 11 were comparable for 2020 and 2019 (1.83 versus 1.78 per 10 000 person-years; P =0.19), while hospitalizations for worsening HF were slightly higher in 2020 versus 2019 (1.04 versus 0.93 per 1000 person-years; P =0.02). In the lockdown period, rates of new-onset HF diagnoses (1.26 versus 2.25 per 1000 person-years) and of hospitalizations for worsening HF (0.63 versus 0.99 per 1000 person-years) were significantly lower in 2020 versus 2019 ( P for both, <0.0001). Mortality was similar before and after the national lockdown for the population with HF. We observed 90 HF patients with diagnosed COVID-19 infection, of whom 37% (95% CI, 23%–50%) died within 15 days. Conclusions: The number of patients hospitalized with worsening HF or diagnosed with new-onset HF was markedly reduced after lockdown but has not yet impacted mortality in HF patients at a population-based level. However, these data raise concerns for a potential undertreatment of HF currently that may impact prognosis in the longer term.